SPATIAL STRUCTURE IDENTIFICATION OF TBO (TROPOSPHERIC BIENNIAL OSCILLATION) AND TBO INDEX IMPLEMENTATION FOR INDO-PACIFIC REGION - SYAHID MUTTAQIN (NIM : 22412004); Pembimbing : Dr. Tri Wahyu Hadi, ANDI
In the context of monsoon, TBO refers to the tendency of strong (weak) monsoon followed by weak (strong) monsoon with the transition occurred before the onset of the monsoon that involves the coupling processes between the atmosphereocean-land in the Indo-Pacific region and it has been described in a conceptual model. This study aims to identify the spatial and temporal structure of TBO uses Season-Sequence Empirical Orthogonal Function (SSEOF) in reference to the conceptual model using four variables, namely Outgoing Longwave Radiation (OLR), zonal wind, Sea Surface Temperature (SST), and moisture transport. The results showed that OLR represents the TBO spatially and temporally since it has a spatial pattern conformance with convective activity in the conceptual model and is independent of the other climate variability such as El NiÃƒÂ±o Southern Oscillation (ENSO), therefore the temporal pattern of OLR is used as a benchmark in the search for the other variables using cosine similarity analysis. Cosine similarity analysis resulting zonal moisture transport as the variable with high temporal pattern conformity with OLR and it can describe the source of moisture for convective activity. When TBO is viewed as the annual variability of the monsoon, the meridional energy transfer between hemisphere occurs through the circulation of the atmosphere and ocean. Thus, it is necessary to review the SST variable that can represent the ocean circulation in the system of TBO. The results of the teleconnection analysis using Empirical Orthogonal Teleconnection (EOT) indicate that the SST has a role on the TBO for a more limited area than those described in the conceptual model. This study proposes a TBO index for Indo-Pacific region (TBOIP) which can analyze the strength and spatial evolution of TBO in the seasonal time scale for the Indo-Pacific region.